Drone based phenotyping of shoot traits in an Urochloa hybrid population - Cardoso Arango, Juan Andrés; Hernández, Luis Miguel; Escobar, Miller; Castiblanco, Valheria (Bioversity International and the International Center for Tropical Agriculture, 2021)
The interspecific breeding program of Urochloa of the Tropical Forages program of the Alliance Bioversity International and CIAT has successfully developed high-yielding stress resistant plants. However, traditional screening methods of plant vigor rely on visual evaluations or destructive measurements. Drone based phenotyping allows faster acquisition of data based on images. From images, traits like cover area, greenness, height, and volume of plants can be recorded at greater throughput than traditional screening methods. Drone based phenotyping for shoot traits such as those previously mentioned has reached methodological maturity and now are routine activities. Hardship to obtain data due to weather conditions, impossibility to reach field sites, among many factors, delay results from the drone phenotyping pipeline of the Tropical Forages Program.